2003
DOI: 10.1002/anie.200350936
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Tetraoxide: Theoretically Predicted and Experimentally Detected

Abstract: The current interest in CO n (n > 2) oxides reflects the growing recognition of their role in different research areas. First, CO n species are key intermediates in the reactions of atomic and molecular oxygen with the lower oxides of carbon, hydrocarbons, and other organic molecules.[1] Furthermore, CO n oxides and their ions are relevant to the chemistry of the terrestrial [2] and planetary [3] atmospheres. More importantly, members of the CO n family are potential high-energy density materials (HEDM), the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…[26][27][28][29] Cacace and co-workers recently reported the experimental detection of this CO 4 molecule. 30 They surmised, based upon their own and previous theoretical studies, that the lower-energy isomer, Figure 1b, would proceed to dissociation without a barrier, and that the D 2d structure, Figure 1c, would thus be the one observed. This work shows that this is a truly metastable molecule and is attractive for further research.…”
Section: Introductionmentioning
confidence: 96%
“…[26][27][28][29] Cacace and co-workers recently reported the experimental detection of this CO 4 molecule. 30 They surmised, based upon their own and previous theoretical studies, that the lower-energy isomer, Figure 1b, would proceed to dissociation without a barrier, and that the D 2d structure, Figure 1c, would thus be the one observed. This work shows that this is a truly metastable molecule and is attractive for further research.…”
Section: Introductionmentioning
confidence: 96%
“…[2][3][4][5][6] What makes a molecular HEDM? Carbon (C), nitrogen (N) and oxygen (O) are very important elements both on Earth and in space.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, study of such HEDMs has never ceased, though the number of successful examples grows slowly because of the synthetic difficulties. [2][3][4][5][6] What makes a molecular HEDM? First, the most feasible pathway of the molecule should release a large amount of energy upon unimolecular decomposition to CO, N 2 or CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides CO and CO 2 that have a well-known direct bearing on human life, the high-order carboxides CO n (n > 2) have been receiving growing attention in the last decades. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] They can be produced in the reactions of oxygen (atomic or molecular) with the lower oxides of carbon, hydrocarbons, and other organic molecules. 26 CO n and their ions are also relevant to the chemistry of the terrestrial 27 and planetary 28 atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Cacace and coworkers reported the rst detection of neutral CO 4 and, based on their own and previous computational studies, assigned it the bicyclic 1 2 structure with a lifetime exceeding 1 ms in the isolated gas state. 15 Later in 2007, Jamieson et al reported on the detection of the monocyclic isomer 1 1 via low temperature infrared spectroscopy of CO 2 ice. 19 CO 4 has also been the subject of other computational 14,17,23,24 and experimental 24 studies.…”
Section: Introductionmentioning
confidence: 99%